2007
DOI: 10.1016/j.ijfatigue.2006.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modelling of the influence of local mixed mode displacements on roughness induced crack closure

Abstract: Application of crack closure analytical modelling to predict the behaviour of complex fatigue crack growth properties is limited partly due to restricted two dimensional modelling approaches. An analytical model of roughness induced crack closure (RICC) is developed in the present paper considering a three dimensional twisted and kinked crack path. Residual shear deformations at asperities in the crack wake affect the crack opening generating closure. These residual shear deformations are explicitly formulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…13f). The phenomenon of crack closure delaying fatigue crack propagation has been observed and reported in the previous studies as well [34,35]. Thus, the crack closure observed in this study may be related to the high Schmid factors and large sizes of the grains, as per the statistical chart of the Schmid factors (see in Fig.…”
Section: Fatigue Crack Path Analysissupporting
confidence: 80%
“…13f). The phenomenon of crack closure delaying fatigue crack propagation has been observed and reported in the previous studies as well [34,35]. Thus, the crack closure observed in this study may be related to the high Schmid factors and large sizes of the grains, as per the statistical chart of the Schmid factors (see in Fig.…”
Section: Fatigue Crack Path Analysissupporting
confidence: 80%
“…On the other hand, various studies have reported that the fatigue crack growth behaviour of aluminium alloys is affected by crack closure effect, particularly near-threshold region [43,44]. Besides, the crack closure effect is greatly influenced by grain size, deflected angle and slip bands [45,46].…”
Section: Fcp Mechanisms At Fatigue Stage Imentioning
confidence: 99%
“…One further thermally activated process influencing FCG rates is crack closure [1,54], most notably oxidation induced crack closure (OICC). OICC can become important if the exposure of surfaces to the environment in the wake of the crack leads to (additional) oxidation that causes a substantial volume expansion.…”
Section: Crack Closurementioning
confidence: 99%